Acne Keloidalis Nuchae is Associated with Cutis Verticis Gyrata - Umar S; Lullo JJ; Carter MJ; Shitabata PK; Lee DJ (Dove Medical Press, 2022)
Sanusi Umar,1- 3 Jenna J Lullo,2 Marissa J Carter,4 Paul K Shitabata,2,5 Delphine J Lee1,2 1Department of Medicine, University of California at Los Angeles, Los Angeles, CA, USA; 2Division of Dermatology, Department of Medicine, Harbor-UCLA Medical Center, Torrance, CA, USA; 3Dr. U Hair and Skin Clinic, Manhattan Beach, CA, USA; 4Strategic Solutions, Inc., Bozeman, MT, USA; 5Dermatopathology Institute, Torrance, CA, USACorrespondence: Sanusi Umar, Dr. U Hair and Skin Clinic, 2121 N. Sepulveda Avenue, Suite 200, Manhattan Beach, CA, 90266, USA, Tel +1-310 318-1500, Fax +1-310 318-1590, Email drumar@dru.comPurpose: Both acne keloidalis nuchae (AKN) and cutis verticis gyrata (CVG) are scalp conditions predominantly affecting men. Both are characterized by dermal thickening and fibroblast hyperactivity. AKN typically occurs in the nuchal area, often involving the naturally occurring folds in the occipital region. The aim of this study was to determine the relationship between excessive scalp folding (CVG) and AKN.Patients and methods: A total of 108 patients with AKN seen over 11 years from July 2009 and November 2020 were retrospectively evaluated. Patients with AKN concomitant with CVG were selected for analysis.Results: Seven of the 108 AKN patients had scalp-wide (widespread) AKN lesions, including 4 with CVG. In 3 of the 4 patients with concomitant AKN and CVG, the AKN was widespread, and its onset had preceded CVG by 1- 2 years. In the fourth CVG patient, AKN lesions were confined to the nuchal area, and the CVG preceded AKN onset by several years. All patients were male, with a mean age of 35.8 years (overall) and 38.0 years (CVG group).Conclusion: We describe a previously unreported relationship between widespread AKN and CVG, with the development of AKN preceding CVG formation.Keywords: transforming growth factor, cicatricial alopecia, fibroblasts, syndromic